Stock Return Predictability: Is it There? - Ang, Andrew; Bekaert, Geert (Review of Financial Studies, 2007)
We examine the predictive power of the dividend yields for forecasting excess returns, cash flows, and interest rates. Dividend yields predict excess returns only at short horizons together with the short rate and do not have any long-horizon predictive power. At short horizons, the short rate strongly negatively predicts returns. These results are robust in international data and are not due to lack of power. A present value model that matches the data shows that discount rate and short rate movements play a large role in explaining the variation in dividend yields. Finally, we find that earnings yields significantly predict future cash flows. (JEL C12, C51, C52, E49, F30, G12)